Relations between executive function and emotionality in preschoolers: Exploring a transitive cognition–emotion linkage - Ferrier, David E.; Bassett, Hideko H.; Denham, Susanne A. (Frontiers in Psychology, 2014)
Emotions play a crucial role in appraisal of experiences and environments and in guiding thoughts and actions. Moreover, executive function (EF) and emotion regulation (ER) have received much attention, not only for positive associations with children’s social-emotional functioning, but also for potential central roles in cognitive functioning. In one conceptualization of ER (Campos, Frankel, & Camras, 2004), processes of ER, and those of emotional expression and experience (hereafter referred to as emotionality) are highly related and reciprocal; yet, there has been little research on young children’s EF that focuses on emotionality, although it is easily observed within a classroom. The two goals of the study were to: (1) investigate the relatively unexplored role of emotionality in the development of EF in early childhood and (2) assess the relations between an observational rating of EF obtained after direct assessment with a standardized EF rating scale. We predicted that observed emotionality and EF would both demonstrate stability and predict one another within and across time. 175 children aged 35-60 months were recruited from Head Start and private childcare centers. Using PLS modeling, we chose T1 emotionality as the exogenous variable and tested pathways between emotionality and EF across two time points, 6 months apart. Results showed that both T1 observed EF and emotionality predicted their respective T2 counterparts, supporting the idea that both constructs build upon existing systems. Further, T1 emotionality predicted T1 observed EF and the T2 BRIEF-P composite. In turn, T1 observed EF predicted emotionality and the T2 BRIEF-P composite. These findings fit with literature on older populations in which EF and emotionality have been related, yet are the first to report such relations in early childhood. Last, observed T1 EF’s positive prediction of the T2 BRIEF-P composite lends credence to the use of both EF measures in applied and research settings.